2022
DOI: 10.1002/jgh3.12719
|View full text |Cite
|
Sign up to set email alerts
|

Acute‐on‐chronic liver failure: Epidemiology, prognosis, and outcome of a multicenter study in Thai population

Abstract: Author contribution: Sakkarin Chirapongsathorn contributed to the review of data for eligibility, evaluation of quality and data extraction; writing the manuscript, data analysis, authorship. Tongluk Teerasarntipan contributed to the review of data for eligibility and data extraction, evaluation of quality. Krit Tipchaichatta contributed to the review of data for eligibility and data extraction, drafting the manuscript. Tanita Suttichaimongkol, Naichaya Chamroonkul, Chalermrat Bunchorntavakul, Sith Siramolpiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Aggressive alcohol intake, alcoholic hepatitis, and bacterial infection were the most common causes of ACLF in alcohol liver disease[ 48 ]. The AUROCs of the CLIF-SOFA, CLIF-OF, and CLIF-C scores showed a slight superior effect in estimating short-term mortality; however, they were equivalent to MELD and MELD-Na[ 49 ]. To clarify this finding, Chirapongsathorn et al [ 49 ] had elevated short- and long-term mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive alcohol intake, alcoholic hepatitis, and bacterial infection were the most common causes of ACLF in alcohol liver disease[ 48 ]. The AUROCs of the CLIF-SOFA, CLIF-OF, and CLIF-C scores showed a slight superior effect in estimating short-term mortality; however, they were equivalent to MELD and MELD-Na[ 49 ]. To clarify this finding, Chirapongsathorn et al [ 49 ] had elevated short- and long-term mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…The AUROCs of the CLIF-SOFA, CLIF-OF, and CLIF-C scores showed a slight superior effect in estimating short-term mortality; however, they were equivalent to MELD and MELD-Na[ 49 ]. To clarify this finding, Chirapongsathorn et al [ 49 ] had elevated short- and long-term mortality rates. In patients with ACLF, as per the CLIF-C definition, the prediction accuracy of the CLIF-SOFA, CLIF-OF and CLIF-C scoring tools were no better than the accuracy of MELD and MELD-Na scores.…”
Section: Discussionmentioning
confidence: 99%
“…In his study, Masnou et al (12) showed that approximately 83 percent of cases had nearly identifiable triggering circumstances gastrointestinal bleeding (53 percent) and infection were the most common triggering causes (19 percent). Sepsis (50 percent) was the most frequent factor that caused ACLF, according to Chirapongsathorn et al (13) across all grades of ACLF, the frequency of multiple organ failures other than liver failure was significantly higher in ACLF patients. The variables that demonstrated a significant correlation with ACLF across grades were total leukocyte count, INR, and serum creatinine.…”
Section: Disscusionmentioning
confidence: 96%
“…Acute on chronic liver failure is a serious clinical syndrome characterized by acute liver dysfunction in patients with chronic liver disease, which has a high mortality rate and poor prognosis (1). In China, hepatitis B virus infection is the leading cause of acute on chronic liver failure.…”
Section: Introductionmentioning
confidence: 99%